Nuevos registros de aberraciones cromáticas en el plumaje de dos especies de aves en zonas urbanas de Hidalgo y Tamaulipas, México - Rodríguez Ruiz, Erick Rubén; Martínez-Sánchez, Itzcóatl; Treviño-Carreón, Jacinto (Instituto de Ecología, A.C., 2015)
We report the first observations of partial leucism in Columbina inca and Quiscalus mexicanus, and also present the first record of albinism in Mexico for Q. mexicanus. We observed the leucistic individuals in human disturbed areas. This suggests that other individuals with chromatic aberration may be observed in non disturbed sites.